Search, evidentiary procedure for discovering and removing documents and material means of evidence - Buzescu, Gheorghe (Eximia, 2024)
The paper deals with the importance of the legislative framework governing domicile search and the procedure by which it can be ordered. Domicile search is decisive in solving the criminal case by obtaining evidence necessary to establish the facts or circumstances in which the crime was committed and to identify the perpetrator. A house search is a criminal procedure in which judicial authorities carry out certain searches of residential premises in order to obtain physical evidence of certain crimes. The searches require "legality" and participation in appropriate procedural safeguards against arbitrariness and abuse in order to respect the human rights enshrined in the Romanian Constitution and also in the European Convention on Human Rights, especially with respect for private and family life. I am trying to analyse to what extent the new legal provisions fall within the guarantees imposed by human rights law. To do this, I look at the search warrant procedure and the legal conditions that judicial authorities must follow during the home search procedure. Domiciliary search is regulated in Articles 157-164 of the NCPP, and in Art. 27 of the Romanian Constitution and art. Article 8 of the ECHR expressly provides that the conduct of this procedure presupposes respect for the inviolability of the person’s domicile and private life.